The Effect of Incisional and/or Intraperitoneal Local Anesthetic Application on Postoperative Pain during Laparoscopic Cholecystectomy - Aydin, Oguz Ugur; Aydin, Eda Uysal; Dandin, Ozgur; Ozer Etik, Diğdem; Cekmen, Nedım; Gogus, Nermin (International Journal of Innovative Research in Medical Science, 2016)
Objective - In this study, we aimed to determine the effect of levobupivacaine (LB) application by intraperitoneal, incisional, and both together on postoperative pain after laparoscopic cholecystectomy. Materials and Methods - One hundred ASA (American Society of Anesthesiologists) I-II patients undergoing laparoscopic cholecystectomy were recruited in the study. The patients were randomized into four groups: placebo group (P), incisional group (I), intraperitoneal group (IP), and the combined (incisional+intraperitoneal) group (C). In the postoperative period, pain in the patients during resting and coughing was evaluated after 30 min, 2, 4, 8, 12, and 24 hours by employing visual analogue scale (VAS) for pain. Applied analgesic quantity, shoulder pain, and the existence of nausea-vomiting were also recorded. Results - Pain scores during resting and coughing were significantly lower in the combined group compared with others. Pain scores were similar in the incision and intraperitoneal groups, whereas in the placebo group were significantly lower. The analgesic need was lowest in the combined group and highest in the placebo group. There was no shoulder pain either in the combined or intraperitoneal groups. Nausea-vomiting rates were similar in all groups. Conclusions - We conclude that combined application of 0.25 % levobupivacaine can be used as an effective and safe method for postoperative pain control after laparoscopic cholecystectomy.